2006
DOI: 10.1007/s11427-006-0123-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of K+ growth conditions on the accumulation of cesium by the bacterium Thermus sp. TibetanG6

Abstract: The accumulation of cesium by the bacterium Thermus sp. TibetanG6 was examined under different K+ growth conditions. The effects of external pH and Na+ on the accumulation of cesium were also studied, and the mechanism involved was discussed. K+ regimes played an important role in the accumulation of cesium by the strain TibetanG6. The quantity of cesium accumulated (24 h) was much higher in K+-deficient regime than that in K+-sufficient regime. The pH and Na+ had different effects on the accumulation of cesiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The Daggyai geothermal field is known for its high cesium (Cs) hot springs and Cs‐bearing geyserites (0.32–1.55 wt.% Cs, data from Zheng, 1989) occurrences. Published work has largely focused on the Cs accumulation mechanism (Wang, Kong, & Zheng, 2006;Wang, Zheng, & Huang, 2007;Wang, Zheng, & Kong, 2012), the location and mobilization of Cs in geyserites (Zhou, Ren, Sherriff, & Yao, 2013), the age of the Cs deposit (Chen & Feng, 1993;Zhao et al., 2006a), the hydrochemical composition of the hot spring waters (Guo, Planer‐Friedrich, Liu, Yan, & Wu, 2019;Liu et al., 2019;Wang, Shen, Liang, Jiang, & Liao, 2015;Zhang, 2014), and the microbial community in the hot springs (Zhang et al., 2018). The fabrics and origin of the host deposit, the Daggyai geyserites, however, have rarely been studied (Zhang, 2007;Zhao et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The Daggyai geothermal field is known for its high cesium (Cs) hot springs and Cs‐bearing geyserites (0.32–1.55 wt.% Cs, data from Zheng, 1989) occurrences. Published work has largely focused on the Cs accumulation mechanism (Wang, Kong, & Zheng, 2006;Wang, Zheng, & Huang, 2007;Wang, Zheng, & Kong, 2012), the location and mobilization of Cs in geyserites (Zhou, Ren, Sherriff, & Yao, 2013), the age of the Cs deposit (Chen & Feng, 1993;Zhao et al., 2006a), the hydrochemical composition of the hot spring waters (Guo, Planer‐Friedrich, Liu, Yan, & Wu, 2019;Liu et al., 2019;Wang, Shen, Liang, Jiang, & Liao, 2015;Zhang, 2014), and the microbial community in the hot springs (Zhang et al., 2018). The fabrics and origin of the host deposit, the Daggyai geyserites, however, have rarely been studied (Zhang, 2007;Zhao et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…TibetanG7 occurred rapidly within the first 5 min, suggesting that uptake occurred to a considerable extent extracellularly. IR spectroscopy indicated that the accumulation of cesium by this bacterium is a process of homeostasis with cesium initially accumulated on the cell wall [26] .…”
Section: Discussionmentioning
confidence: 98%
“…They may not be growing in K + -sufficient condition, and thus may be induced to some extent to K + -deficient cells. It is known that K + -regimes play a significant role in cesium accumulation by microorganisms [22,26] , and microorganisms accumulate much more cesium in K + -deficient cells than in K + -sufficient cells. Therefore, higher levels of cesium accumulation by bacterium Thermus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Culture experiments indicated that all the dominant cyanobacteria in the Daggyai geothermal area have the ability to accumulate Cs extracellularly and intracellularly through biosorption (Wang et al, 2006(Wang et al, , 2007(Wang et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%